Organizational corruption: conceptual typology, continuum of destructiveness, and rationalization - Rodrigues, Caio César Coelho (2022)
This thesis comprises three articles seeking to understand the multiple meanings of corruption, based on organizational theory and the Odebrecht case. The first article conducts an integrative literature review of the corruption concept, creating a typology of corruption and providing a better definition of corruption as a theoretical construct that transcends an empirical phenomenon. The second article seeks to understand the corruption concept within a corrupt culture. Specifically, it reformulates the continuum of destructiveness and presents rationalization and moral disengagement as better concepts to understand the corruption perpetuation in organizations. This article empirically supports theories showing that agents, at different stages of the continuum, rationalize corruption differently. The third article empirically summarizes and validates the rationalization mechanisms. It contributes to the literature by investigating how corruption perpetrators rationalize corruption and how they deconstruct that cognitive process when facing charges. While the integrative literature review remains theoretical, the other two articles present empirical analyses based on Odebrecht’s collaborations. The use of judicial data from the Odebrecht case can help organizational scholars overcome the lack of reliable data on corruption.